Sigma level choice examination in executing incline Lean Six Sigma (LSS) within the material and item material industry - Kurnia, Hibarkah; Wiyatno, Tri Ngudi; Nugroho, Bayu Hari; Nuryono, Arif (Operations Excellence: Journal of Applied Industrial Engineering, 2025)
Many manufacturing industries in the world use the Lean Six Sigma (LSS) approach in analyzing and improving waste activities and reducing production defects. The Textile and Product Textile (TPT) industry can also be easily implemented because this industry is a labor-intensive industry. However, in its development, no one has analyzed the sigma level in the TPT industry by reviewing studies. The sigma level obtained from various sources and various types of TPT industries cannot yet be concluded about the sigma level value for each type of industry. This research points to look at writing articles related to LSS, particularly within the TPT industry. This inquire about employments the clustering strategy, specifically a refinement research strategy taken within the TPT industry within the writing review. This ask around found dispersions of 55 articles that were effectively studied inside the composing with the Six Sigma technique being the preeminent broadly utilized and more explore objects based on the tall quality of 41 articles. Gathering by industry section is the piece of clothing industry with 14 articles that reinforce the LSS. In the interim, based on nation groupings, the biggest number is Indonesia with 19 articles. It is trusted that this inquire about commitment can ended up a reference for anybody who will utilize LSS within the fabricating industry.